Accounting and Legal Disputes in Islamic Banking and Finance - Kadi, Sanaa (Journal of Islamic Economic Laws, 2025)
This paper explores the role of accounting for Islamic finance in dispute settlements in the Islamic banking and finance (IBF) industry. This study adopts a legal approach, using an analysis design to investigate the main principles and processes of dispute resolution in Islamic finance. The study involves a comprehensive review of relevant legal sources, including Islamic law, national laws and regulations, court judgments, legal opinions, and industry standards. The study shows that the promotion of legal certainty will require a strong base of legal and Islamic finance professionals and the competence and awareness of accountants, lawyers,​ and judges. The study also shows that financial records, statements, and documentation have a significant role in resolving disputes. Accounting records can provide evidence of transactions and terms agreed upon. Properly documented and transparent accounting practices can help clarify the nature of the dispute and contribute to finding a fair and efficient resolution in the context of Islamic financial activities. This study provides practical implications for IBF stakeholders in managing legal disputes, such as helping Islamic financial practitioners recognize the importance of integrating robust accounting practices, clear financial reporting, and transparent disclosure mechanisms. These practices are pivotal not only for the industry’s credibility but also for effective disputes resolution.